THE DEVELOPMENT RESEARCH OF THE FISHING BOAT DISTINCTION TECHNIQUE BY SATELLITE-ONBOARD HIGH RESOLUTION OPTICAL SENSOR — DISTINCTION TECHNIQUE USING IKONOS DATA - T. Moriyama; H. Tameishi; J. Suwa; S. Kanno; Y. Sugimori; T. Osawa; M. Koiwa (BRIN, 2004)
This paper describes the vessel distinction algorithm by using radiance silhoutte algorithm for IKONOS data. Although original TKONOS image has high spatial resolution about 1 m, it is difficult to identify whole feature of the vessel. The newly developed algorithm named